Correlation Between Self-Rated Health and Socioeconomic and Psychological Charasteristics of Ambulatory and Hospitalized Patients Over 44 Years of Age - Joana Simeonova; Angelika Velkova; Silvia Tsvetkova; Penka Kostadinova; Petkana Hristova; Mariela Kamburova (Journal of Biomedical & Clinical Research)
The aim of the study was to identify socioeconomic and psychological determinants of self-rated health among ambulatory and hospitalized patients. A cross-sectional study was carried-out in 2014. Two hundred and twelve patients over 44 years of age filled in a self-administrated questionnaire. Self-rated health (SRH) was measured by 5-point range scale. The level of well-being (WB), sources of social support, personal financial capacity, social status, etc. were studied as well. Data were processed by SPSS.v.19. Parametric and non-parametric statistical methods were applied. Over 70% of patients evaluated their health as fair and good. The persons with higher WB had higher SRH, that correlation was moderate (r=0.452; p=0.001). In regard to the social status the differences were significant - the unemployed, old age retirees or ill health retirees evaluated their health lower (p0.05). Identification of socioeconomic and psychological factors of self-rated health allows clarifying better their effect mechanisms and planning appropriate health services